Evaluation of the drought tolerance level of Malaysian indica rice genotypes using biochemical markers at reproductive stage - Evamoni, Fatematuz Zuhura; Nulit, Rosimah; Ibrahim, Mohd Hafiz; Sidek, Noorhazira; Kong Yap, Chee; Yong Seok Yien, Christina (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2023)
Drought is a serious limiting factor to rice (Oryza sativa L.) production in Malaysia, and becoming a more significant issue with respect to the global climate change. This study selected 15 widely cultivated Malaysian indica rice genotypes whose drought tolerance level is still unknown. The study aimed to determine the changes in some biochemical responses of selected rice genotypes under drought condition was designed in completely randomized design in rain-out shelter. The results showed that all genotypes had significantly increased total soluble sugar (TSS), proline, catalase (CAT), ascorbate peroxidase (APX) and membrane electrolyte leakage (EL) upon drought stress. The study revealed maximal 154.88% and 166% increase in CAT and APX respectively during the stress. However, MR167 showed maximal 46.79% decrease in total chlorophyll and MARDI WARNA98 revealed maximal 41.95% decrease in total protein as a result of water stress. The correlation analysis among the biochemical traits under drought condition showed positive and significant relationship except EL. Multivariate principal component analysis (PCA) showed that total protein and TSS were important criteria for identifying drought-tolerant genotypes. MR185, MR211, MR253, MR269, MR284, MR303, and MR307 had better performances in all of the biochemical analyses and contributed better to most of the variations in the study.